Low energy and high energy dumps for ELI-NP accelerator facility: rational and Monte-Carlo calculationsș results - Esposito A.; Frasciello O.; Pelliccioni M. (EPJ Web of Conferences, 2017)
ELI-NP will be a new international research infrastructure facility for laser-based Nuclear Physics to be built in Magurele, south west of Bucharest, Romania. For the machine to operate as an intense γ rays’ source based on Compton back-scattering, electron beams are employed, undergoing a two stage acceleration to 320 MeV and 740 MeV (and, with an eventual energy upgrade, also to 840 MeV) beam energies. In order to assess the radiation safety issues, concerning the effectiveness of the dumps in absorbing the primary electron beams, the generated prompt radiation field and the residual dose rates coming from the activation of constituent materials, as well as the shielding of the adjacent environments against both prompt and residual radiation fields, an extensive design study by means of Monte Carlo simulations with FLUKA code was performed, for both low energy 320 MeV and high energy 720 MeV (840 MeV) beam dumps. For the low energy dump we discuss also the rational of the choice to place it in the building basement, instead of installing it in one of the shielding wall at the machine level, as it was originally conceived. Ambient dose equivalent rate constraints, according to the Rumenian law in force in radiation protection matter were 0.1 /iSv/h everywhere outside the shielding walls and 1.4 μiSv/h outside the high energy dump area. The dumps’ placements and layouts are shown to be fully compliant with the dose constraints and environmental impact.